(untitled) (Proceedings of Southern Federal University. Philology, 2012)
Bezgina J.S. Keywords: criticism, women’s literature, nationality, Russian woman’s image, Russian soul. The article is devoted to the analysis of the critical works of A.V. Zrajevskay from the ideological and artistic points of view. The research allows to considerably extend problematics of her works and to reflect critical views of the writer on such actual problems for her time, as the problem of female creativity, the state of the Russian literature, the authentic Russian culture and the idea of nationality, the education and the role of women in contemporary society. Her critical article «On Novel Reading» is under scientific analysis for the first time.